PARIWISATA BUDAYA DI DESA WISATA BUUN SEJATI KABUPATEN LOMBOK BARAT - Harnika, Ni Nyoman; Sutriani, Ida Ayu Nyoman (Institut Agama Hindu Negeri Gde Puda Mataram, 2022)
This study aims to determine the implementation of cultural tourism in Buun Sejati Tourism Village, West Lombok Regency. This study uses a qualitative method, with a field study approach, namely mapping the potential and existing conditions of the Buun Sejati Tourism Village, then looking for links with the phenomena and concepts of cultural tourism. The data collection method used is divided into three: First, observation in the form of direct observation related to the existing condition of Buun Sejati Tourism Village as a cultural tourism destination. Second, interviews with managers, the public sector, Pokdarwis and local communities. Third, study documentation sourced from articles, books and references that are relevant to the research topic. The data analysis technique uses an inductive approach to help interpret the various data obtained. The results of this study indicate that there are three indicators in the implementation of cultural tourism, including (1) Instilling tourism awareness to the younger generation. (2) Organizing cultural events. (3) Cultural Tourism through Sapta Pesona. However, there are obstacles in the implementation of cultural tourism, namely (1) the absence of certified human resources (2) the lack of cultural tourism facilities and infrastructure.